Annual Plant Reviews Online 2019
DOI: 10.1002/9781119312994.apr0666
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Regulatory Mechanisms for Efficiency and Prevention of Photo‐Oxidative Stress

Abstract: Regulatory mechanisms of photosynthesis affecting light capture, the efficiency of electron transport, and the distribution between linear and alternative electron transport routes are needed to balance energy input with metabolic demands. Rapid fluctuations in light intensity lead transiently to absorption of excess light energy, requiring immediate regulation, whereas adverse environmental conditions over longer‐term require acclimation responses. In either case, excitation of photosynthetic pigments beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 212 publications
1
33
0
Order By: Relevance
“…Nonphotochemical quenching (NPQ) is a general term for mechanisms that regulate how much light energy is available for photosynthesis [ 3 ]. NPQ is considered important in preventing elevated formation of reactive oxygen species (ROS) that otherwise could occur during excess light absorption [ 4 , 5 ]. The so-called qE component of NPQ, which reduces quantum yields of chlorophyll fluorescence in the light-harvesting antennae, is the dominant thermal dissipation pathway driven by pH changes in the thylakoid lumen [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonphotochemical quenching (NPQ) is a general term for mechanisms that regulate how much light energy is available for photosynthesis [ 3 ]. NPQ is considered important in preventing elevated formation of reactive oxygen species (ROS) that otherwise could occur during excess light absorption [ 4 , 5 ]. The so-called qE component of NPQ, which reduces quantum yields of chlorophyll fluorescence in the light-harvesting antennae, is the dominant thermal dissipation pathway driven by pH changes in the thylakoid lumen [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although acclimated to a light intensity higher than 100 µmol photons m -2 s -1 , ex vitro plants displayed some level of oxidative stress also after the low light treatment, showing that acclimation clearly has a cost even if adjusting to lower light intensities. This result was unexpected considering that photooxidative stress is usually associated to conditions of excessive light intensities (Li et al, 2018;Roach & Krieger-Liszkay, 2019). However, several works have shown that short-term low light can also induce oxidative stress, as measured by different indicators (Yu et al, 2016;Li et al, 2017;Zhu et al, 2017), although the molecular mechanisms involved in this specific condition is not as well understood as for high light.…”
Section: Discussionmentioning
confidence: 96%
“…Despite possessing a variety of light screening pigments, there are times when the amount of light that reaches the photobiont exceeds that which can be used in photosynthesis. This can be problematic because, as discussed above, excess light energy results in elevated levels of ROS produced by chlorophyll ( 1 O 2 ) and electron transport chains (O 2 .− and H 2 O 2 ), thus leading to photo-oxidative damage (Roach & Krieger-Liszkay 2019). Photobionts use several processes to regulate the efficiency at which light energy is used, which are collectively referred to as non-photochemical quenching (NPQ).…”
Section: Avoidance Of Ros Formation By Regulating Light-use Efficiencymentioning
confidence: 99%